مستوى إدراك أساتذة التعليم الابتدائي لصعوبتي تعلم القراءة والكتابة - دراسة ميدانية ببعض ابتدائيات بلدية عين الحجل بالمسيلة - - فيلالي فاطمة; معمري عمر; اشراف: صلهد فتيحة (جامعة محمد بوضياف -المسيلة, 2025)
هدفت هذه الدراسة للكشف عن مستوى إدراك أساتذة التعليم الابتدائي لصعوبتي القراءة والكتابة، تحقيقا لهذا الهدف تم إتباع المنهج الوصفي، حيث طبقت الدراسة على عينة عشوائية ذات المرحلتين (عنقودية وبسيطة) تكونت من (79) أستاذ وأستاذة تعليم ابتدائي ببعض ابتدائيات عين الحجل المسيلة حيث تم استخدام استمارة استبيان مكونة من 28 عبارة لصاحبه دخوش المبروك (2020)، وقد أسفرت نتائج الدراسة على ما يلي: - مستوى إدراك أساتذة التعليم الابتدائي لصعوبات القراءة والكتابة مرتفع ومنه عدم تحقق الفرضية. - لا توجد فروق ذات دلالة في إدراك صعوبات القراءة والكتابة بين الذكور والإناث وبالتالي عدم تحقق الفرضية البحثية. - لا توجد فروق ذات دلالة إحصائية في إدراك صعوبات القراءة والكتابة تبعا لمتغير الخبرة المهنية وبالتالي عدم تحقق الفرضية البحثية. - لا توجد فروق ذات دلالة إحصائية في إدراك صعوبات القراءة والكتابة تبعا لمتغير المؤهل العلمي وبالتالي عدم تحقق الفرضية البحثية الكلمات المفتاحية: مستوى الإدراك، صعوبة القراءة، صعوبة الكتابة، أستاذ التعليم الابتدائي.   Abstract: This study aimed to reveal the level of perception of the reading and writing difficulties by the primary school teachers. In order to achieve this objective, the descriptive analytical approach was adopted, as the study was applied to a random sample consisting of (79) male and female primary education teachers in some of the primary schools in Ain al-Hajjal al-M’sila, using a questionnaire form consisting of 28 phrases, and the results of the study resulted in the following: - The level of perception of the reading and writing difficulties by the primary education teachers is high, including the non-fulfillment of the hypothesis. - There are no significant differences in the perception of reading and writing difficulties between males and females and therefore the research hypothesis is not fulfilled. - There are no significant differences in the perception of reading and writing difficulties, depending on the variable of professional experience, thus not fulfilling the research hypothesis. - There are no significant differences in the perception of reading and writing difficulties depending on the educational qualification variable and, consequently, the research hypothesis is not fulfilled Keywords: perception level, reading difficulty, writing difficulty, primary school teacher.